Effects of Vaccination Against Coccidiosis on Gut Microbiota and Immunity in Broiler Fed Bacitracin and Berry Pomace - Das, Quail; Shay, Julie; Gauthier, Martin; Yin, Xianhua; Hasted, Teri-Lyn; Ross, Kelly; Julien, Carl; Yacini, Hassina; Kennes, Yan Martel; Warriner, Keith; Marcone, Massimo F.; Diarra, Moussa S. (Frontiers in Immunology, 2021)
Feeding practices have been found to influence gut microbiota which play a major role in immunity of poultry. In the present study, changes in cecal microbiota and humoral responses resulting in the 55 ppm bacitracin (BACI), 1% each of cranberry (CP1) and wild blueberry (BP1) pomace alone or in combination (CP+BP) feeding in broiler Cobb 500 vaccinated or not against coccidiosis were investigated. In the non-vaccinated group, no significant treatment effects were observed on performance parameters. Vaccination significantly affected bird’s performance parameters particularly during the growing phase from 10 to 20 days of age. In general, the prevalence of coccidiosis and necrotic enteritis (NE) was reduced by vaccination (P < 0.05). BACI-treated birds showed low intestinal lesion scores, and both CP1 and BP1 feed supplementations reduced Eimeria acervulina and Clostridium perfringens incidences similar to BACI. Vaccination induced change in serum enzymes, minerals, and lipid levels in 21-day old birds while, levels of triglyceride (TRIG) and non-esterified fatty acids (NEFA) were higher (P < 0.05) in CP1 treated non–vaccinated group than in the control. The levels of NEFA were lower in BACI- and CP1-fed birds than in the control in non-vaccinated day 28 old birds. The highest levels of all estimated three immunoglobulins (IgY, IgM, and IgA) were found in the vaccinated birds. Metagenomics analysis of the cecal bacterial community in 21-day old birds showed the presence of Firmicutes (90%), Proteobacteria (5%), Actinobacteria (2%), and Bacteroidetes (2%). In the vaccinated group, an effect of BACI was noted on Proteobacteria (P = 0.03). Vaccination and/or dietary treatments influenced the population of Lactobacillaceae, Enterobacteriaceae, Clostridiaceae, and Streptococcaceae which were among the most abundant families. Overall, this study revealed that besides their beneficial effects on performance, alike bacitracin, berry pomaces in poultry feed have profound impacts on the chicken cecal microbiota and blood metabolites that could be influenced by vaccination against coccidiosis.